2013
DOI: 10.1096/fj.12-219634
|View full text |Cite
|
Sign up to set email alerts
|

Targeting sphingosine kinase 1 attenuates bleomycin‐induced pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive interstitial lung disease, wherein transforming growth factor β (TGF-β) and sphingosine-1-phosphate (S1P) contribute to the pathogenesis of fibrosis. However, the in vivo contribution of sphingosine kinase (SphK) in fibrotic processes has not been documented. Microarray analysis of blood mononuclear cells from patients with IPF and SphK1- or SphK2-knockdown mice and SphK inhibitor were used to assess the role of SphKs in fibrogenesis. The express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(143 citation statements)
references
References 45 publications
(57 reference statements)
7
136
0
Order By: Relevance
“…S1P levels are elevated in the BAL fluid of patients with IPF and bleomycin-challenged mice (43). S1P levels are regulated by a synthetic pathway mediated by two isoforms of sphingosine kinases (SphKs), SphK1/2, that phosphorylate sphingosine and generate S1P, and by the catabolic pathways that break down S1P because of the actions of S1P lyase and other lipid phosphatases (28). Our recent study revealed that the expression of SphK1 was increased in lung-tissue samples from patients with IPF and bleomycin-challenged mice (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…S1P levels are elevated in the BAL fluid of patients with IPF and bleomycin-challenged mice (43). S1P levels are regulated by a synthetic pathway mediated by two isoforms of sphingosine kinases (SphKs), SphK1/2, that phosphorylate sphingosine and generate S1P, and by the catabolic pathways that break down S1P because of the actions of S1P lyase and other lipid phosphatases (28). Our recent study revealed that the expression of SphK1 was increased in lung-tissue samples from patients with IPF and bleomycin-challenged mice (28).…”
Section: Discussionmentioning
confidence: 99%
“…S1P levels are regulated by a synthetic pathway mediated by two isoforms of sphingosine kinases (SphKs), SphK1/2, that phosphorylate sphingosine and generate S1P, and by the catabolic pathways that break down S1P because of the actions of S1P lyase and other lipid phosphatases (28). Our recent study revealed that the expression of SphK1 was increased in lung-tissue samples from patients with IPF and bleomycin-challenged mice (28). SphK1 is a known effector of the TGF-b-mediated signal transduction and expression of profibrogenic molecules in bleomycin-challenged lung tissue and in human lung fibroblasts (44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrin alpha(v)beta3, commonly expressed in platelets, is involved in Rho GTPases mediated activation of sphingosine-1-phosphate (S1P) endothelial cell chemotaxis (35) and also acts as a receptor for another gene in the set, Von Willebrand Factor. S1P activity has been shown to be involved in the onset of pulmonary fibrosis (36,37). Interestingly, integrin alpha(v)beta6, also linked to pulmonary fibrosis via Rho-mediated signaling (38)(39)(40) is not included in the magenta module.…”
Section: Gene Co-expression Modules Associate With Clinical Traits Mmentioning
confidence: 99%